Optimasi Kombinasi Bahan Makanan untuk Mencegah Stunting pada Balita dengan menggunakan Algoritme Genetika - Tria Melia Masdiana Safitri; Imam Cholisoddin; Budi Darma Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The number of good nutrients provided to kids in Indonesia has been a common problem and has yet to be solved. The lack of nutritional intake can cause malnutrition and stunting (the lack of height growth). Indonesia has become the fifth biggest country in terms of the numbers of toodlers suffering stunting, whose numbers have risen to nearly 9 million toddler. Stunting in toddlers can be caused by many factors, one of which is the lack of knowledge possessed by the parents of the combination of a variety of food ingredients which must be fed to the toddler in order to provide a perfectly balanced supply of nutrients. Providing a single dish does not always provide a perfectly balanced supply of nutrients. Providing a stable supply of perfectly balanced nutrients can be achieved by a variety of food ingredient combinations that contain roughly the same amount of nutrients. In this research, a recommendation of food compositions was provided through the course of 7 days using a genetic algorithm to assist parents in combining food ingredients which corresponded with a toddler's nutritional needs. Based on the testing parameters of the genetic algorithm, the optimal results from the combination of Cr:Mr test was 0,7:0,3 and the fitness results had an average score of 97,412. The testing results on the optimal size of the population was discovered to be 90 with an average fitness score of 96,95. Testing of the most optimal number of generations that need to be generated were 350 generations with an average fitness score of 96,664. The result of the test was capable of saving the parents expenses as much as 35,77% with the average cost of a dish was Rp.19269,21.